Pengaruh Customer Perceived Quality, Persepsi Harga Dan Social Media Marketing Terhadap Ticket Purchase Intention (Studi Kasus pada Sounds of Downtown Music Festival) - Savitri, Devi; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the effect of perceived quality, perceived price, and social media marketing on purchase intention at Sounds of Downtown Music Festival. The sampling technique using purposive sampling obtained a sample of 95 respondents. The data collection method uses a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that simultaneously perceived quality, perceived price, and social media marketing positively and significantly affected purchase intention. Likewise, partially perceived quality, perceived price, and social media marketing positively and significantly affect purchase intention. Keywords: Perceived Quality, Perceived Price, Social Media Marketing, Purchase Intention.